OFQuality: a quality of service management module for software-defined networking. (2019) - Volpato, Felipe; Silva, Madalena Pereira Da; Dantas, Mario Antonio Ribeiro
The exponential growth of online devices has been causing difficulties to network management and maintenance. At the same time, we have noticed that applications are getting richer in terms of content and quality, thus requiring more and more network guarantees. To overcome this issue, new network approaches such as Software-Defined Networking (SDN), have emerged. OpenFlow, which is one of the most used protocols for SDN, is not enough to provide QoS based on queue prioritisation. In this paper we propose an architecture of a controller module that implements the Open vSwitch Database Management Protocol (OVSDB) in order to provide QoS management with queue prioritisation. Our module differs from others because it features mechanisms to test and facilitate user configuration. Our experiments showed that our module behaved as expected, causing few delays when managing switch elements, therefore making a useful tool for QoS management on SDN.